Conceptual and Biofunctional Embodiment: A Long Story on the Transience of the Enduring Mind - Iran-Nejad, Asghar; Irannejad, Auriana B. (Frontiers in Psychology, 2017)
We examine how embodiment in biological activity is different from conceptual embodiment as reflected in classic, modern, and postmodern perspectives on tacit knowledge. The central theme of the essay is how understanding is embodied conceptually and biofunctionally. We focus (a) on how biofunctional understanding is different from conceptual understanding and (b) on how the overall differences between these two types of embodied understanding are complementary. We show here from a conceptual perspective that embodiment theories have diverged on the meaning of embodiment; but convergence may be more likely across future perspectives if we first redefine the construct of tacit knowledge as tacit understanding and then define (explicit) conceptual understanding as being directly grounded in tacit understanding, for the purpose of comparison with biofunctional understanding defined as being grounded in biological activity. We illustrate the complementary differences between conceptual and biofunctional embodiment of understanding first in the absence of language and then using a particular statement format and the implicit analogy of biofunctional embodiment in other bodily systems. We conclude with a suggestion about the directly uncovered but highly related embodiment of language in a section on a future direction.